Avaliação energética econômica da cultura do milho em assentamento rural, Iperó-SP - Almeida, Luiz Carlos Ferreira de [UNESP]; Bueno, Osmar de Carvalho [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP] (EIA Energy in Agriculture, 2010)
This paper, having as a hypothesis that greater energetic inputs don't keep ratio with economical outputs, has tried to study the economical and energetic flows in the maize cultivation to several production systems used in Ipanema Settling Area I, having as analysis instrument the indexes of Cultural, Energetic, Economical efficiency, which were added to the methodological proposal of Cultural Economical and Energetic Economical Efficiency indexes, built for probability settings. Four different systems have been identified: "A", "B", "C" and "D". The energetic expenditure were, respectively, 4,836.19 MJ x ha-1, 4,4647.17 MJ x ha-1, 4,639.49 MJ x ha-1 and 4,450.47 MJ x ha-1. In "A", where the use of machines is more intensive, the participation of biological source energy was 23.26%, whereas the ones of fossil origin are 76.74%. The "D" system has the greatest Cultural Efficiency, with average index of 16.26, whereas "A" showed the lowest Cultural Efficiency indexes, with average values of 14.83. For the analysis of the Energetic Efficiency, that indicates the dependence of energy from non renewable sources, the highest index was the "D" system with an average index of 53.84. The Economical Efficiency Indexes, which ranged from 1.84 to 1.96, show that all systems are efficient. The "D" system, with index equal to 8.84, showed the highest index of Economical Cultural efficiency. The Economical Energetic analysis for "A", "B", "C" and "D" systems, has resulted, respectively, in the following indexes: 21.14 ; 23.86 ; 22.87 and 29.26. Through the outcome analysis, it was concluded that the more intensive use of energy from nonrenewable sources ("A" system) didn't necessarily mean a higher efficiency when compared to "D" (labor intensive), what comes to prove the paper's initial hypothesis.

Tendo como hipótese que maiores inputs energéticos não guardam proporção com outputs econômicos, este trabalho estudou os fluxos energéticos e econômicos da cultura do milho, para os diversos sistemas de produção existentes no Assentamento Ipanema Área I, tendo como ferramental os índices de eficiência Cultural, Energética e Econômica, acrescidos da proposta metodológica dos índices de Eficiência Cultural Econômica e Energética Econômica construídos para cenários probabilísticos. Foram identificados quatro sistemas diferentes: "A", "B", "C" e "D", com dispêndios energéticos, respectivamente, de 4.836,19 MJ x ha-1, 4.4647,17 MJ x ha-1, 4.639,49 MJ x ha-1 e 4.450,47 MJ x ha-1. Em "A", no qual o uso de máquinas é mais intensivo, a participação da energia de fonte biológica foi de 23,26%, enquanto os de origem fóssil foi de 76,74%. O sistema "D" possui a maior Eficiência Cultural, com índice médio de 16,26, enquanto "A" apresentou os menores índices de Eficiência Cultural, com valores médios de 14,83. Para análise da Eficiência Energética, indicativo da dependência de fontes não-renováveis, o maior índice foi o sistema "D", com índice médio de 53,84. Os Índices de Eficiência Econômica, variando entre 1,84 e 1,96, mostraram que todos os sistemas foram eficientes. O sistema "D", com índice igual a 8,84, apresentou o mais alto índice de eficiência Cultural Econômica. A análise Energética Econômica para os sistemas "A", "B", "C" e "D", resultou, respectivamente, nos índices de 20,80 , 23,61 , 22,87 e 29,26. Concluiu-se que o uso mais intensivo de energia de fontes não-renováveis (sistema "A") não se traduziu necessariamente numa maior eficiência, quando comparado ao "D" (intensivo de mão-de-obra), o que comprova a hipótese inicial do trabalho.
Energy and economic valuation of maize planting in rural settlement, Iperó/SP
Keywords: Economical energetic analysis; Energetic balance; Energetic efficiency; Rural settling; Maize; Avaliação energética econômica; Balanço energético; Eficiência energética